Targeting TREM2 for Parkinson’s Disease: Where to Go? - Li, Xiao-xian; Zhang, Feng (Frontiers in Immunology, 2021)
Genome-wide association studies (GWAS) found that myeloid cell-triggered receptor II (TREM2) is second only to apolipoprotein E4 (APOE) as a major risk factor for Alzheimer's disease (AD). Rare missense mutations in TREM2 (rs75932628, p.R47H) significantly increase the risk of AD. AD-associated pathologic proteins are present in most clinically diagnosed Parkinson's disease (PD) patients. Currently, numerous population genetic tests have shown that polymorphisms in TREM2 are associated with a variety of neurodegenerative diseases. Is TREM2 also highly associated with PD risk? Due to the complex pathogenesis of PD, there is still no effective drug treatment. TREM2 has received increasing widespread attention as a potential therapeutic target. This review focused on the variation of TREM2 in PD and the role of TREM2 in PD pathogenesis to further provide evidence for new immune-related biomarkers and therapies for PD.